Factors influencing small holder farmers adoption of climate SMART agriculture practices in Welmera Woreda, Central Ethiopia - Gudina, Mesay Hailu; Alemu, Esubalew Abate (Frontiers in Climate, 2024)
Adoption of climate smart agriculture practices believed significantly lessened the devastating impact of climate change on agriculture. However, in developing countries like Ethiopia, adoption and use level remains low. Understanding farmers' levels of CSA practice adoption and influencing factors is therefore crucial. The goal of the study was to evaluate the degree to which various CSA practices were being used in the study area, as well as adoption determinants. The study was conducted in Welmera district, Oromia, Ethiopia. Three kebeles were chosen from the district, and a random sample of 306 farmers was picked. We utilized a cross-sectional household survey, a focus group discussion, and interviews with key informants. A multivariate probit model was employed to investigate factors influencing adoption of multiple climate-smart agriculture practices. According to the result, Conservation agriculture, integrated soil fertility management, and crop diversification are the most often used CSA practices. The results also revealed that men farmers outperformed female farmers in terms of crop diversity and improved animal feed and feeding practice adoption. Farmers' age has a considerable and unfavorable impact on their likelihood of adopting improved soil fertility management and crop diversification. However, it has a positive and considerable impact on the adoption of agroforestry practices. According to economic factors, having a relatively big farmland area considerably enhances the adoption of conservation agriculture, enhances soil fertility management, crop diversity, improved livestock feed and feeding methods, and postharvest technology practice. Improved livestock feed and feeding are more likely to be used if farm income is higher. Having significant number of animals strongly promotes conservation agriculture adoption, and access to financial services positively impacts agroforestry, diversification of crops, and postharvest technology practice adoption. Furthermore, institutional factors including access to the agricultural extension services and trainings were discovered important and beneficial for crop diversification; similarly, access to field day participation was discovered to have a significant and positive impact on the adoption of conservation agriculture and improved soil fertility management practices. It is critical to raise awareness about climate change among farmers and experts, as well as to incorporate location-specific CSA practices into agricultural programs.